2016
DOI: 10.1038/modpathol.2015.146
|View full text |Cite
|
Sign up to set email alerts
|

The presence of intraductal carcinoma of the prostate in needle biopsy is a significant prognostic factor for prostate cancer patients with distant metastasis at initial presentation

Abstract: Intraductal carcinoma of the prostate is an adverse prognostic factor in localized prostate cancer patients. However, whether it influences outcome of those patients with distant metastases discovered at initial diagnosis is unclear. Here, we evaluated whether the presence of intraductal carcinoma of the prostate in prostate needle biopsies is an adverse prognostic factor for cancer-specific survival and overall survival in such prostate cancer patients. We retrospectively enrolled 150 eligible patients. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 35 publications
6
72
0
Order By: Relevance
“…Both of them did not demonstrated the presence of IDC‐P and was a prognostic factor by multivariate analysis, although they showed it was a prognostic factor by univariate analysis. Our previous study showed that the incidence of IDC‐P was 36.3% in the needle biopsy of patients with high‐risk prostate cancer and 50.5% in radical prostatectomy specimens from high‐risk patients, while the incidence was 66.7% in patients with prostate cancer and a distant metastasis . Later, Porter et al reported IDC‐P frequencies in a large database of 23.1, 36.7, and 56.0% in the intermediate‐risk, high‐risk, and metastatic or recurrent disease risk categories, respectively; this result is almost the same as in our previous study.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Both of them did not demonstrated the presence of IDC‐P and was a prognostic factor by multivariate analysis, although they showed it was a prognostic factor by univariate analysis. Our previous study showed that the incidence of IDC‐P was 36.3% in the needle biopsy of patients with high‐risk prostate cancer and 50.5% in radical prostatectomy specimens from high‐risk patients, while the incidence was 66.7% in patients with prostate cancer and a distant metastasis . Later, Porter et al reported IDC‐P frequencies in a large database of 23.1, 36.7, and 56.0% in the intermediate‐risk, high‐risk, and metastatic or recurrent disease risk categories, respectively; this result is almost the same as in our previous study.…”
Section: Discussionmentioning
confidence: 85%
“…We previously reported for the first time that the presence of IDC‐P in radical prostatectomy specimens is the only prognostic factor for high‐risk prostate cancer in terms of PFS and CSS. IDC‐P in needle biopsies could also become an adverse prognostic factor for PSA‐PFS, CSS, and OS in patients with prostate cancer and a distant metastasis at the initial diagnosis . A Chinese group and a Norwegian group also recently discussed the relationship between presence of IDC‐P on diagnostic needle biopsy and a high risk of mortality in localized and metastatic prostate cancer patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting common understanding, besides the recognition of IDC‐P, is the strong association of IDC‐P with high‐grade and high‐volume invasive prostate cancer (PCa). Previous studies have associated IDC‐P with a poor prognosis and shorter biochemical‐recurrence‐free survival . Our group reported that IDC‐P is an adverse prognostic factor for patients with high‐risk or metastatic PCa patients .…”
Section: Introductionmentioning
confidence: 66%
“…Van der Kwast et al recommended the presence of IDC‐P in a needle biopsy as a predictive factor for patients with intermediate‐ and high‐risk PCa treated by radiotherapy. Moreover, we previously reported that the presence of IDC‐P was the only prognostic factor for the progression free survival, cancer‐specific survival, and overall survival; those results were obtained from a multivariate analysis of patients who underwent radical prostatectomy and had distant metastasis at their initial presentation . As these studies make clear, IDC‐P correlates with increased stage and prognosis .…”
Section: Discussionmentioning
confidence: 94%